Design and Modeling of Metamaterial-Based Antenna Arrays for Nanosatellite Communication Systems - Hemsy, Axel (2025)
The design and modeling of compact antenna arrays based on metamaterials for nanosatellitecommunication systems is presented. The main objective is to optimize performance at 2.45 GHz (S-Band). As a first step, a single coaxially fed antenna was designed on a Rogers RO4350B substrate (0.76 mm thick, εᵣ = 3.48). A unit cell with Minkowski fractal geometry was incorporated into the ground plane, and two opposite corners of the patch were truncated to induce right-hand circular polarization. Different antenna arrays were designed in 1×2 (45 × 185 mm), 1×4 (48 × 155 mm), and 2×2 (75 × 85 mm) configurations, all with the same thickness of 0.76 mm. The feeding networks were implemented using Wilkinson power dividers. These arrays enabled an increase in gain to 5.1 dBi, 5.21 dBi, and 5.8 dBi, as well as an improvement in axial ratio, while maintaining efficiencies between 71% and 78%. The useful bandwidths obtained (VSWR < 2, S₁₁ < -10 dB, axialratio < 3 dB) were 22 MHz, 39 MHz and 27 MHz. The compact dimensions allow integration with the structure and subsystems onboard a CubeSat: the 1×2 and 2×2 arrays are with a 1U format, while the 1×4 can be integrated into a 2U format.